Xylanase Supplementation in Wheat-based Diets and the Influence on Necrotic Enteritis in Broilers: A Translational Model for Human Malnutrition - Beer Lesleigh; Butler Leasea; Gautier Alyson; Graham Danielle; Teague Kyle; Wilson Venus; Sami Dridi (Advances in Food Technology and Nutrition Sciences, 2018)
In the poultry industry, necrotic enteritis results in substantial production and economic losses each year. Outbreaks are more prevalent due to the removal of antibiotic growth promoters.1Clostridium perfringens, a commensal organism within the gastroin-testinal tract of poultry, is the primary bacterial etiology respon-sible for necrotic enteritis.